Benjamin Franklin - American Writers 19 : University of Minnesota Pamphlets on American Writers - Hornberger, Theodore, 1906-1975 (Book collections on Project MUSE., 1962)
Benjamin Franklin - American Writers 19 was first published in 1962. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.